2013
DOI: 10.1021/ac401537k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Surface-Enhanced Raman Scattering Flow Detector Using Hydrodynamic Focusing

Abstract: Label-free, chemical specific detection in flow is important for high throughput characterization of analytes in applications such as flow injection analysis, electrophoresis, and chromatography. We have developed a surface-enhanced Raman scattering (SERS) flow detector capable of ultrasensitive optical detection on the millisecond time scale. The device employs hydrodynamic focusing to improve SERS detection in a flow channel where a sheath flow confines analyte molecules eluted from a fused silica capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 51 publications
(106 reference statements)
2
70
0
Order By: Relevance
“…Applications using SERS as the research tool can be found in the fields of analytical chemistry, surface science, and biomedical studies [4][5][6][7][8][9]. Most of the SERS studies have been carried out with molecules adsorbed on the surfaces of transition metals [10][11][12][13], particularly Ag and Au.…”
Section: Introductionmentioning
confidence: 99%
“…Applications using SERS as the research tool can be found in the fields of analytical chemistry, surface science, and biomedical studies [4][5][6][7][8][9]. Most of the SERS studies have been carried out with molecules adsorbed on the surfaces of transition metals [10][11][12][13], particularly Ag and Au.…”
Section: Introductionmentioning
confidence: 99%
“…SERS-active substrates were incorporated into a custom-built flow cell by affixing individual substrates onto a standard microscope glass slide, as described before, 31 and shown in Figure S-1 (ESI). One end of a 72 μm i.d., 143 μm o.d.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…22 Our recent work demonstrated that sheath-flow SERS detection lowers the limit of detection of rhodamine to concentrations of 10 −9 –10 −10 M and enables high throughput online detection in CZE. 31, 32 This suggests that sheath-flow SERS may enable high sensitivity characterization of more common analytes.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of periodic nanostructures by nanometer-scale lithography techniques can achieve moderate sensitivity and high reproducibility, but it is currently limited to research laboratories due to its high cost and complications associated with the fabrication of SERS-active substrates. In order to make SERS more applicable, the synergistic integration of SERS with micro-fluidics has been carried out [13][14][15]. However, micro-fluidic SERS also introduces additional complexity to the fabrication of these devices and time-consuming, so far, this technique is impractical to meet the needs for sensitive, ultra-low-cost disposable analytical devices.…”
Section: Introductionmentioning
confidence: 99%